Oscillation of the Impulsive Hematopoiesis Model with Positive and Negative Coefficients (Baghdad Science Journal, 2024)
In this paper, the problem of oscillating solutions for an impulsive hematopoiesis model with positive and negative coefficients is investigated. There are several evolutionary processes, which frequently encounter dramatic shifts at specific times and are sensitive to short-term perturbations. As a result, we construct several oscillation criteria that are either brand-new or enhance many of recent findings in the literature. We also give illustrations of how impulsiveness affects the oscillating solutions of the hematopoiesis model.